Dancing to the Bhangra in New York City - Anjali Gera Roy (Transatlantica)
Nearly two decades after Rekha Malhotra alias DJ Rekha launched Basement Bhangra, a “party that mixes South Asian bhangra music with hip-hop, dancehall and electronic sounds to create an unforgettable New York City dance experience” at SOB’s on Varick Street, which subsequently moved to Le Poisson Rouge, it has been voted by Time Out New York readers as the “best live music venue”. Born in London and raised in Queens and Long Island, Brooklyn based DJ Rekha, who is credited with pioneering bhangra, had been invited to perform at events like P.S. 1’s Warm Up Series, Central Park’s Summerstage, Prospect Park’s Celebrate Brooklyn, Brooklyn Museum’s First Saturdays, and the annual flagship Loving Day celebration held in New York City, recognized by Newsweek as one of the most influential South Asians in the US and received accolades from The New York Times, CNN, The Fader, The Village Voice, and The Washington Post.  With Rekha being invited to deejay at major public events in NYC, bhangra could claim to be officially inducted in the global city’s soundscape. The recognition of Basement Bhangra and DJ Rekha by mainstream media, academia and policymakers signals the claims of desis to the space of New York city through the performance of a vibrant South Asian youth subculture that originated in the villages of Punjab in North India. Drawing on Henri Lefebvre’s notion of the production of space, this essay focuses on a performance space to argue that the dancing in the city interrupts its spatial coordinates.